An integrated folded-patch antenna for wireless microsystems - Mendes, P. M. (2004)
A fully integrated, folded-patch antenna for operation at 5.62 GHz and application in wireless sensor networks has been realized and characterized. Overall dimensions of 4x4x1 mm3, measured bandwidth of 100 MHz and an efficiency of 32% were achieved. The antenna fabrication is based on wafer-level packaging techniques and consists of two adhesively bonded glass substrates with through substrate electrical vias and 3-D metallization. The measured electrical characteristics of the antenna prototype fit well with the simulations.